Exploring the Intrinsic and Extrinsic Motivations Behind Electric Motorcycle Adoption in Yogyakarta, Indonesia - Dimas B. E. Dharmowijoyo; Muhammad Zudhy Irawan; Nindyo C. Kresnanto; Sakinah F. Shalihati; Anugrah Illahi (Journal of the Civil Engineering Forum, 2025)
The rapid rise in motorcycle usage in Indonesia has contributed significantly to urban transport emissions, underscoring the need for cleaner alternatives such as electric motorcycles (EM). This study investigates the roles of extrinsic motivation (e.g., policy incentives) and intrinsic motivation (e.g., residential location, daily activity patterns, and psychological readiness) in shaping EM adoption in Yogyakarta, Indonesia. A stated preference survey was conducted with 400 conventional motorcycle owners, collecting socio-demographic data, four-day activity diaries, perceived accessibility measures, and responses to a transtheoretical model questionnaire. Using a mixed logit modelling framework, three models were estimated, progressively incorporating vehicle attributes, policy incentives, spatiotemporal factors, travel satisfaction, and behavioural readiness stages. Results show that spatial context, particularly residing farther from the city centre, public transport, and parks, has a stronger effect on EM adoption than readiness stage, with workaholic activity patterns also positively associated. Among policy measures, free battery replacement emerged as more influential than free annual vehicle tax, although range, maintenance cost, and charging time remained more critical determinants. Behavioural readiness moderates these effects: individuals in the preparation stage are significantly more likely to adopt EMs, while those in contemplation are less inclined. The findings suggest that beyond financial incentives, campaigns emphasizing EM reliability and environmental benefits, targeted toward suburban residents and high-usage riders, could accelerate adoption. These insights support spatially and behaviourally segmented strategies for promoting low-emission transport in motorcycle-dependent, rapidly motorizing cities, and inform the potential integration of market-based mechanisms such as personal carbon trading or tradable driving credits.